FAKTOR-FAKTOR YANG MEMPENGARUHI INDIKATOR PENENTUAN KELAYAKAN DAN KESESUAIAN LOKASI PEMBANGUNAN PULAU KECIL BERBASIS SISTEM SOSIAL-EKOLOGI - Yudi Wahyudin; Mahipal; Dudi Lesmana (JURNAL MINA SAINS, 2022)
Small island development requires a targeted approach so that it can be carried out according to the characteristics of the small island's social-ecological system. This study aims to identify the factors that influence the feasibility assessment indicators and the suitability of small island development sites based social-ecological system. The study was conducted using a survey approach to 24 experts in their respective fields who have relevance to the development of small islands in Indonesia. The results showed that there were 24 factors that could affect the indicators of the feasibility assessment and the suitability of the small island development location. Natural resources and ecosystems, facilities, human resources, accessibility, tourist sites, local wisdom, island governance, clean water, security, social capital, carrying capacity, and strategic position are the 12 most influential factors. Based on the priority analysis of SSE components, the most influential on the feasibility and suitability of small island development sites based on social-ecological systems are small island resources (1.00), associated small island ecosystems (0.81), small island users (0.60), socio-political-security-sovereignty (0.26), small island infrastructure (8.01%), and small island infrastructure providers (0.21). These factors and the level of influence of the SSE component are expected to be input in determining the indicators of feasibility and suitability of small island development sites based on social-ecological systems.